Mato Grosso do Sul e Campo Grande: articulações espaço-temporais - Le Bourlegat, Cleonice Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2000)
The framework of this study was to comprehend the specific conditions surrounding the incorporation and political-economical consolidation of the state of Mato Grosso Sul to the national scenario, during the cyclic evolution of the capitalistic system as well as the role of Campo Grande in this process. The origin and evolution of Campo Grande were analyzed in the context of possible relations between urbanization, regional development and the integration of the state in the national scope. In this approach, several theoretical compatible formulations were considered as to systemic view of reality, from the complex and dynamic point of view. This implies a multi scale reasoning, associating spatial dimension to the historical one, in a theoretical- methodological effort of comprehend the logic between the general and the specific. It was possible to verity peculiarities attributed to Mato Grosso do Sul in the general laws of the capitalistic system, and instances capable of explaning the local effects of the intervention of industrial economy in the dynamic of the process analysed since colonial times, as well as the role of Campo Grande in this process, especially in relation to the economical integration of the state territory to the rest of the nation.

A preocupação norteadora desse trabalho foi a de conhecer as condições específicas em que se deram a incorporação e consolidação econômica-política de Mato Grosso do Sul ao espaço nacional, durante a evolução cíclica do sistema capitalista, assim como papel de Campo Grande nesse processo. A origem e evolução de Campo Grande foram analisadas no conjunto das considerações, buscando-se possíveis relações entre urbanização, desenvolvimento regional e integração do Estado ao espaço nacional. Na abordagem, levaram-se em conta diversas formulações teóricas compatíveis no que tange à visão sistêmica da realidade, do ponto de vista de sua complexidade e dinamicidade. Implica num raciocínio multiescalar, associando-se a dimensãoespacial à histórica, num esforço teórico-metodológico de apreensão dialética entre o geral e o particular. Foi possível verificar na dinâmica do processo analisado desde o período colonial, particularidades que couberam a Mato Grosso do Sul nas leis gerais do sistema capitalista, capazes de explicar os efeitos locais da intervenção da economia industrial, assim como o papel que coube a Campo Grande nesse processo, especialmente com relação à integração econômica do território do Estado ao espaço nacional.
Keywords: Geografia regional - Campo Grande (MS); Mato Grosso do Sul - Geografia; Campo Grande (MS) - Geografia